Karakteristik diare pada anak di RSUP Sanglah Denpasar tahun 2017 - I Dewa Made Satrianjaya; Ni Nyoman Metriani Nesa; Dewi Sutriani Mahalini (DiscoverSys Inc., 2019)
Background: Diarrhea is one of the most common diseases affecting children around the world. In Indonesia, the national rate of diarrhea prevalence is 9% where 16.7% of cases occur at 1-4 years old and 16.5% of cases at under one year old. In addition, dehydration causes most mortalities. Aim: This study aims to determine the characteristics of diarrhea in children in Sanglah General Hospital, Denpasar. Method: Thisstudyis a cross-sectional study design using secondary data from the register data in the Pediatric Division of Sanglah General Hospital Denpasar from January to November 2017. Of the 170 data, there were 165 survival samples. Characteristics of diarrhea in children are described using tables, pie charts, and graphs.Result: Most of the sample were males (56.5%), infants (40%), patients from Denpasar (55.3%) and those with good nutritional status (60%). The mean age of the patient was 26.6 months, the mean body weight was 10.6 kg, and the mean height was 79.8 cm. Most of them were diagnosed with acute diarrhea (98%), where the most common cause is a viral infection (75%). The most common comorbid diseases are congenital heart disease and neurological disease (10.6%). Most patients have only mild dehydration (57%). Long term treatment of diarrhea patient in child wards mostly for 2-3 days.Conclusion: Diarrheain children in Sanglah Denpasar Hospital period January-November 2017 most suffered by men and babies, mostly from Denpasar. Most of them have acute diarrhea that is mainly caused by a viral infection.